Traditional Pest and Disease Management Practices in Sikkim Himalayan Region - Gopi, R.; Avasthe, R. K.; Kalita, H.; Kapoor, Chandan; Yadav, Ashish; Babu, Subhash; Das, S. K. (International Journal of Bio-resource and Stress Management, 2023)
Local knowledge or Indigenous Technical/Traditional knowledge (ITK) is the knowledge belonging to a specific community or local group and that the people in a given community have developed over time, and still continue to develop. Agriculture and allied activities continue to be an important occupation and form the main base of the economy in Sikkim. There are various pests and diseases in crop plants which cause severe loss in yield resulting in reduced production. Farm folk of Sikkim follow number of traditional pest management practices for managing pests and diseases of various crops. A study was conducted during June 2013 to 2015 on traditional pest and disease control measures adopted by the farmers in Sikkim. Different itks like use of wood ash, kerosene, table salt, lime, cow urine, cow dung, some unique indigenous plants and indigenous techniques like insertion of bamboo pegs were used by the farmers for the management of various insect pests and diseases occurring in Sikkim. Besides, people also use some indigenous pest and disease resistant varieties of large cardamom, maize, buckwheat and tomato. This report is an attempt to document some of the indigenous practices followed by traditional farmers for the management of pests and diseases of major crops grown in Sikkim. The practices collected in this study will be of great help to the people of Sikkim as the state has been declared recently as organic farming state.